THE INFLUENCE OF ANIMATED VIDEO MEDIA ON PREGNANT WOMEN'S KNOWLEDGE ABOUT DANGER SIGNS OF PREGNANCY - Sari, Ruri Maiseptya; Suhita Tri Oklaini; Dewi Aprilia Ningish I; Nanda Desra Purwanti (Poltekkes Kemenkes Medan, 2023)
Dangers in pregnancy need to be recognized and detected early so that they can be handled properly because every danger sign in pregnancy can result in complications in pregnancy. the aim of this research is to study the effect of animated video media on pregnant women's knowledge about the danger signs of pregnancy. pregnant in the working area of the Telaga Dewa Community Health Center, Bengkulu city. This research method uses a pre-test approach using one group pre-test and post-test design. The population of this study was only pregnant women, all pregnant women at the Telaga Dewa Community Health Center, Bengkulu City from January to April 2023, totaling 176 pregnant women. The sample consisted of 33 pregnant women whose samples were taken purposively. Data collection uses secondary and primary data. Data analysis was carried out using univariate tests, data normality tests, bivariate tests, and Wilcoxon tests. The search results obtained were: (1) Average knowledge before being given health education was 46.09; (2) The average knowledge after being given health education is 82.97. Research conclusions There is an influence of animated video media about danger signs in pregnancy in the work area of the Medan Telaga Dewa Community Health Center, Bengkulu City